2013
DOI: 10.1017/s0950268813001428
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up ofHelicobacter pyloriinfection in children over two decades (1988–2007): persistence, relapse and acquisition rates

Abstract: Helicobacter pylori culture on gastric biopsy was performed on 4964 subjects aged <18 years from 1988 to 2007 at a central laboratory in Brussels. The total number of biopsies increased markedly from 941 in 1988-1993 to 1608 in 2004-2007. Biopsies were repeated at least once for 922 subjects (603 initially negative and 319 initially positive for H. pylori). Persistence rate of H. pylori at 1 year after initial positive biopsy was greater in the 1998-2007 cohort than in the 1988-1997 cohort (72.7% vs. 45.8%, P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
0
16
1
Order By: Relevance
“…[5][6][7][8][12][13][14] No significant change was seen in the metronidazole resistance rates in the consecutive years. The high rate of metronidazole resistance was detected in this region (75.20%), where resistance rate was higher than that in other regions of China and other countries (from 10.1% to 61.6%).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[5][6][7][8][12][13][14] No significant change was seen in the metronidazole resistance rates in the consecutive years. The high rate of metronidazole resistance was detected in this region (75.20%), where resistance rate was higher than that in other regions of China and other countries (from 10.1% to 61.6%).…”
Section: Discussionmentioning
confidence: 92%
“…The rate of resistance to clarithromycin in children varies among different countries, such as 18.8% in South Korea, 15 11.9%-34.7% in Europe 5,7,12,13 , and 21.6% in Austria. The prescription of this drug in children during the last decade for respiratory tract infections might contribute to a high resistance rate of H. pylori to clarithromycin.…”
Section: Discussionmentioning
confidence: 99%
“…Vanderpas et al (2014) found that the prevalence of H. pylori was 18.2% in children aged <6 years and 49.3% in adolescents aged 12-17 years. Ertem et al (2013) found …”
Section: Discussionmentioning
confidence: 97%
“…29,30 Vanderpas et al reported that the reinfection after eradication for the period of 5 years amounted to 48.6%, and new infections that occurred in the period of 10 years in previously negative people amounted to 38.7%. 30 The risk of acquiring the infection was fourfold higher in non-European than in European children (p < 0.001). Other authors have also reported H. pylori seroconversion.…”
Section: Infection Transmission and Reinfectionmentioning
confidence: 99%